Disparate ability of murine CD8α(−) and CD8α(+) dendritic cell subsets to traverse endothelium is not determined by differential CD11b expression - Colvin, Bridget L (Blackwell Science Inc, 2004)
Upon Ag uptake and response to maturation stimuli, dendritic cells (DC) are directed through lymphatic or blood vessel endothelium to T cell areas of secondary lymphoid tissues by the constitutively expressed CC chemokines CCL19 and CCL21. We have shown that mature (m) murine CD8α(+) DC exhibit poorer migratory ability to these chemokines than classic CD8α(–) DC by quantifying their in vitro chemotaxis through unmodified Transwell® filters. We hypothesized that lower surface expression (compared to CD8α(–) mDC) of the adhesion molecule CD11b on CD8α(+) DC might limit their ability to adhere to filter pores in vitro and/or endothelium in vitro/in vivo. To test the role of this and/or other adhesion molecules (CD11a, CD31, CD54 and CD62L) in regulating murine DC subset migration, we used specific mAbs to block their function and quantified their migration through resting or tumour necrosis factor (TNF)-α-activated endothelial cell (EC) layered-Transwell® filters. Both CD8α(+) and CD8α(–) subsets migrated through resting EC (albeit less than in the absence of EC) in response to CCL19 and CCL21, and migration through TNF-α-activated EC was enhanced. In contrast to reports concerning human DC, transendothelial migration of the murine DC subsets was not dependent on CD11b, CD31, or CD62L expression by these cells. CD54 and CD11a, however, were at least partly involved in DC/EC interactions. This is the first report to examine adhesion molecules involved in transendothelial migration of murine DC subsets.